Jojo's bizarre adventure. Part 6, Stone Ocean. Volume 4 - Araki, Hirohiko, 1960- (Shonen Jump manga., 2024)
The legendary Shonen Jump series is now available in deluxe hardcover editions featuring color pages! The true reason Ermes is in prison is revealed--to seek revenge for her sister's murder by killing Sports Maximum! Jolyne rushes to stop her before she makes the biggest mistake of her life. But unbeknownst to either of them, Sports Maximum is host to the Stand Limp Viscuit. After a vicious battle, Jolyne is sent to the maximum security disciplinary wing. But like a true Joestar, she does not intend to let her fight to save her father's life end there. She continues to hone her strength--that is, until, Father Pucchi sets loose a number of Stand users in search of the mysterious bone that Jolyne once held in her possession. All hell breaks loose as prisoners and guards start murdering each other, and Jolyne takes this opportunity to escape. Meanwhile, F.F. enlists the help of an unlikely, dangerous ally to help save Jolyne: the murderous Anastasia, who is hell-bent on...marrying Jolyne?